SISTEM INFORMASI PELAYANAN PENDAFTARAN PASIEN RAWAT INAP DI PUSKESMAS MENGGUNAKAN PEMOGRAMAN PHP - Haris Nizhomul Haq; Akrom Muhajir; Dicky Iskandar Sobari (STMIK SUBANG, 2022)
This research discusses the development of an Inpatient Patient Registration Service Information System at Community Health Centers (Puskesmas) using PHP programming, as well as implementing DFD (Data Flow Diagram) and ERD (Entity Relationship Diagram) models. The system is designed to enhance efficiency and accuracy in the inpatient patient registration process, covering patient information management, bed availability scheduling, and coordination among medical staff. The DFD model diagram is utilized to illustrate the data flow within the system, while the ERD is employed to detail the relationships between entities in the database. The implementation of this system employs PHP programming to ensure code reliability and readability. The research results indicate that the system can expedite the patient registration process, improve information management, and optimize the utilization of inpatient beds. This study is expected to make a positive contribution to improving healthcare services at Community Health Centers and provide a foundation for the development of similar systems in a broader healthcare service environment. Consequently, the research findings are anticipated to offer significant benefits in enhancing the efficiency and effectiveness of inpatient patient registration services.